Monkeys monitor human goals in a nonmatch-to-goal interactive task. - Rossella Falcone (Public Library of Science (PLoS), 2012)
We designed a new task, called nonmatch-to-goal, to study the ability of macaque monkeys to interact with humans in a rule-guided paradigm. In this task the monkeys were required to choose one of two targets, from a list of three. For each choice, they were required to switch from their choice on the previous trial to a different one. In a subset of trials the monkeys observed a human partner performing the task. When the human concluded his turn, the monkeys were required to switch to a new goal discarding the human's previous goal. We found that monkeys were very skillful in monitoring goals, not only of their own choice by also those of their human partner. They showed also a surprising ability to coordinate their actions, taking turns with the human partner, starting and stopping their own turn following the decision of the human partner in the task.